BETWEEN EUROPE AND LATIN AMERICA: RODRIGO MERCEDES, PSYCHOLOGIST PIONEER (2012)
Assuming the influence that the research of MercedesRodrigoBellidohas had on the psychology and Spanish and Colombian pedagogy, we are going to explain this research. Our overall objective was to make visible the figure of the author through the revision of hes work, as well as the writings of other authors have left it as Fania Smith, who prepared hes doctoral thesis around this semi-occult psychologist. Following a review of selected texts we find that the figure of Mercedes Rodrigo Bellido was especially important for the Colombian Psychology, and her main contribution was the creation of the first training program in psychology, which could extend throughout Latin America. She also was the author of many important contributions especially related to building bridges between the European and Spanish psychology, or the realization that psychology had to have its own field of work, since their contents were being approached from various fields such as medicine or theology. In Spain, also had an important role in the beginnings of Applied Psychology. All these important contributions from Mercedes Rodrigo Bellido opposite with the limited attention so farthis eminent psychologist Madrid has had on our field of knowledge.